Vapor cooling of a structural skirt for a large-scale hydrogen tank. Issue 1 (1st May 2022) - Johnson, W L; Balasubramaniam, R; Hibbs, R
Abstract: The demonstration of vapor cooling on a structural skirt was one of the main objectives of the Structural Heat Intercept, Insulation, and Vibration Evaluation Rig (SHIIVER) testing. SHIIVER consisted of a 4-meter diameter stainless steel tank with an aluminum forward skirt. The forward skirt was cooled by directing effluent vapor from the tank through two flow channels that each went 360 degrees around the interior of the skirt in a helical pattern. Flow rates, temperatures, and pressures in the system were measured allowing for the calculation of heat load removed via cooling stream and heat load reduction into the tank. Testing occurred at fill levels between 25% and 90% full using both liquid hydrogen and liquid nitrogen. Boil-off rate was varied independent of the skirt performance by adding multilayer insulation over the spray-on-foam insulation on the tank domes, while leaving the barrel insulated only with spray-on-foam. The results from the testing, which demonstrate vapor cooling removed heat flow from the tank flange and reduces total propellant heat load by as much as 19%, are analyzed and discussed.